Long‐term weight loss after colorectal cancer diagnosis is associated with lower survival: The Colon Cancer Family Registry. Issue 23 (25th August 2017) - Kocarnik, Jonathan M.; Hua, Xinwei; Hardikar, Sheetal; Robinson, Jamaica; Lindor, Noralane M.; Win, Aung Ko; Hopper, John L.; Figueiredo, Jane C.; Potter, John D.; Campbell, Peter T.; Gallinger, Steven; Cotterchio, Michelle; et al.
Abstract : BACKGROUND: Body weight is associated with colorectal cancer (CRC) risk and survival, but to the authors' knowledge, the impact of long‐term postdiagnostic weight change is unclear. Herein, the authors investigated whether weight change over the 5 years after a diagnosis of CRC is associated with survival. METHODS: CRC cases diagnosed from 1997 to 2008 were identified through 4 population‐based cancer registry sites. Participants enrolled within 2 years of diagnosis and reported their height and weight 2 years prior. Follow‐up questionnaires were administered approximately 5 years after diagnosis. Associations between change in weight (in kg) or body mass index (BMI) with overall and CRC‐specific survival were estimated using Cox regression analysis adjusted for age, sex, American Joint Committee on Cancer stage of disease, baseline BMI, nonsteroidal anti‐inflammatory drug use, smoking, time between diagnosis and enrollment, and study site. RESULTS: At the 5‐year postdiagnostic survey, 2049 participants reported higher (53%; median plus 5 kg), unchanged (12%), or lower (35%; median ‐4 kg) weight. Over a median of 5.1 years of subsequent follow‐up (range, 0.3‐9.9 years), 344 participants died (91 of CRC). Long‐term weight loss (per 5 kg) was found to be associated with poorer overall survival (hazard ratio, 1.13; 95% confidence interval, 1.07‐1.21) and CRC‐specific survival (hazard ratio, 1.25; 95% confidence interval, 1.13‐1.39). Significantly lower survival was similarly observed for relative weight loss (>5% vs ≤5% change), BMI reduction (per 1 unit), or BMI category change (overweight to normal vs remaining overweight). CONCLUSIONS: Weight loss 5 years after a diagnosis of CRC was found to be significantly associated with decreased long‐term survival, suggesting the importance of avoiding weight loss in survivors of CRC. Future research should attempt to further evaluate this association, accounting for whether this weight change was intentional or represents a marker of declining health. Cancer 2017;123:4701‐4708 . © 2017 American Cancer Society . Abstract : Weight loss 5 years after a diagnosis of colorectal cancer appears to be significantly associated with decreased subsequent long‐term survival. The results of the current study suggest the importance of avoiding weight loss in survivors of colorectal cancer.